Keefektifan Model Pembelajaran Talking Stick Berbantu Media Geoboard untuk Meningkatkan Hasil Belajar Matematika Bangun Datar Kelas IV SDN 01 Tambirejo Kabupaten Grobogan - Arni Jumiati; Aries Tika Damayani; Diana Endah Handayani (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study aims to describe improving the learning outcomes of mathematics learning outcomes in the fourth grade elementary school graders through the Talking Stick learning model assisted by Geoboard media. This research is a quantitative research with Pre-Experiment Designs in the form of One-Group Pretest-Posttest Designs. This research was carried out in the fourth grade of SDN 01 Tambirejo, Grobogan Regency in the 2020/2021 academic year during September 2021. The sampling technique used the Probability Sampling technique, so that the fourth grade consisted of 20 students as the experimental class and the fourth grade consisted of 20 students as the control class. The data from this research are in the form of student learning outcomes obtained by using pretest-posttest questions. Based on the research data, the average value of the experimental class (pretest) was 69.3 students who achieved 60% completeness and the average score (posttest) was 75.7 students who achieved 100% completeness. the increase of students in achieving completeness is 40%. From the research data = 9,669 while = 2.042 (dk = 38). Thus > (9,669 > 2.042). This means that the Talking Stick model with the help of Geoboard media is effective on student learning outcomes.